Wake excitation of plasma and electromagnetic oscillations by a relativistic electron bunch in a plasma resonator - Balakirev, V.A.; Onishchenko, I.N. (Problems of Atomic Science and Technology, 2023)
The process of the excitation of plasma and electromagnetic oscillations by a relativistic electron bunch in a plasma resonator is considered. It is shown that the potential electric field of plasma oscillations contains the field of a bulk wake plasma wave and the fields of two surface plasma oscillations. Surface plasma oscillations are localized in the vicinity of the input and output ends of the plasma resonator. In a plasma resonator, as a result of the effect of transition radiation at the ends of the resonator, the electron bunch will also excite eigen electromagnetic oscillations of the resonator. The spatio-temporal structure of the electromagnetic field of these oscillations has been studied. Досліджено процес збудження плазмових та електромагнітних коливань релятивістським електронним згустком у плазмовому резонаторі. Показано, що потенційне електричне поле плазмових коливань містить поле об'ємної кільватерної плазмової хвилі та поля двох поверхневих плазмових коливань. Поверхневі плазмові коливання локалізовані поблизу вхідного та вихідного торців плазмового резонатора. У плазмовому резонаторі в результаті ефекту перехідного випромінювання на торцях резонатора електронний згусток також збуджує власні електромагнітні коливання резонатора. Досліджено просторово-часову структуру електромагнітного поля цих коливань.